RESISTENSI ORANG RIMBA (Studi Tentang Perlawanan Orang Rimba Menghadapi Kebijakan Rencanan Pengelolaan Taman Nasional Bukit Duabelas Propinsi Jambi) - , BURLIAN SENJAYA SH.I, Drs. Haryanto, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Orang Rimba as indigenous communities thatâs live in the area of Bukit Duabelas National Park in Jambi Province, they activity can not be separated from the forest. At least two important issues that cause they life can not be separated from the forest. The First, the economic problems thatâs become the foundation of survival as a place of hunting, gathering, and to use forest products became the most important economic resource in their activity. Second. Forest becomes the identity of life in running a variety of wisdom traditions and culture that bequeathed by the founding fathers as a guide in carrying out the significance of life for Orang Rimba. Management Planning of Bukit Duabelas National Park (RPTNBD) issued by office of Natural Resources Conservation (BKSDA), Jambi Province, by dividing the park into six different zones (core zone, Rimba zone, Traditional zone, Tourism zone, Used Limited zone, and Rehabilitation zone) and put the dynamics life of Orang Rimba only on traditional zone, causing Orang Rimba have a great process of marginalization from their own natural resources, so that the right to fight back, Orang Rimba did resistance to the demands to restore of economic rights and identity rights, with the birth of RPTNBD policy. This research is using case study, through a qualitative approach, this study found that the cause of resistance against the policy of The RPTNBD by Orang Rimba, due to the implementation of policies that are not able to accommodate the interests of Orang Rimba. Orang Rimba who are in the region was not as an asset for the sustainability of ecosystem conservation areas. The policy of RPTNBD more forward the ecological economic aspects rather than considering the culture of indigenous peoples living within the conservation area, and the policy is causing Orang Rimba loss of economic resources and the right to carry identity is full of tradition and culture. This study also, the authors found to deal with these RPTNBD policy, Orang Rimba fought Individual Resistence who later evolved into a collective movement. Collective resistance is a form of protest demonstrations, formal resistance, and is customary resistance, in collective resistance thatâs very urgent is role of some NGOs, especially to build the character of Orang Rimba, the mobilization of the movement, the network and the assistance in every movement of resistance, so resistance is considered effective in voicing demands, while the individual resistance is more closed and the behavior of everyday people are disappointed of Orang Rimba against regulations made by the government policies in RPTNBD. The findings of this study confirm what is presented by Gurr that people can make resistance when he felt something stolen or respect for his way of life threatened by new developments, besides that, Scott also explains the existence of 'state simplification' where countries trend to legalize and regulate public policy that is too strict and uniform for its own sake, in the middle of groups of different people because of their cultural plurality. So, nothing wrong according to Scott on the already marginalized communities such as this is, they will take the fight either overtly or with the concept of everyday resistance which tends more closed (every day forms of Resistance).